CUSTOMER SATISFACTION ANALYSIS AND IT’S INFLUENCE TO LOYALTY AND WORD OF MOUTH ACTIVITY OF AN NUUR HERBAL MEDICINE’S CUSTOMER - Rahmania Hidayati; Sampurno Sampurno; Djoko Wahyono (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Increase of public interest in using herbal medicine causes increase in the number of herbal medicine producers and the competition will be harder. Marketing concept states that companies have to satisfy their consumers in order to gain profits. The satisfied consumers will be loyal to certain products or companies, and they will buy the products again in the future. The more important things is that they will carry out word of mouth activity about the products to people around them. The aims of this research were to know the influence of consumers’ satisfaction on their loyalty, the influence of their satisfaction on their word of mouth behavior, and the influence of their loyalty on their word of mouth behavior. The subjects of this research were the consumers of An Nuur’s herbal medicine in Yogyakarta. This research was conducted by survey with questionnaire as an instrument. The samples were taken with non probability sampling design with purposive sampling procedure. The sample consisted of 65 respondents and was taken from November 2011 to May 2012. The criteria of the respondents were they who had used An Nuur’s herbal medicine at least three times, bought it from stores in Yogyakarta, aged at least 17, and agreed to be subjects of this research. Then, the data were analyzed using linear regression analysis to know the relation between variables. The hypothesis was tested using t test. The result of this research showed that consumers’ satisfaction had significant positive influence on their loyalty. The highest consumers perception was the easiness in consuming An Nuur’s herbal medicine, while the lowest consumers perception was the easiness in purchasing An Nuur’s herbal medicine. Consumers’ satisfaction had significant positive influence on their word of mouth behavior. Consumers’ loyalty had significant positive influence on their word of mouth behavior. Consumers’ loyalty had greater influence than their satisfaction on their word of mouth behavior.Keywords: Satisfaction, loyalty, word of mouth, An Nuur.